AGAINST KANT: toward an inverted transcendentalism or a philosophy of the doctrinal. Issue 4 (1st October 2016) - Tritten, Tyler
Abstract: F.W.J. Schelling's late distinction between negative and positive philosophy correlates negative philosophy with critical philosophy, which delimits what could be said of things without yet actually being able to do so. Positive philosophy, however, is able to make assertions about the actual existence of such objects without transgressing Kant's prison of finitude, i.e., without moving from an immanent, subjective and transcendental position to a transcendent (read: noumenal) object. Schelling's later positive philosophy rather asserts that one begins outside Kant's prison. This is not a dogmatism or, more properly, a dogmatizing philosophy, that attempts to reach the transcendent from an immanent locus, transcendental subjectivity, but it is a "doctrinal philosophy" that begins in transcendence and then has as its task the consequent construction of the domain of transcendental subjectivity. By this means, Schelling's positive philosophy, which he also deems a "historical" and "progressive" philosophy, exposes what Quentin Meillassoux has termed "the great outdoors." Schelling, however, does not show how one might acquire access to this absolute outside, but he argues that one should depart from it. Transcendence is not the aim of knowledge but the absolute prius from which positive, i.e., progressive, philosophy begins.